Anti-inflammatory activity of Acanthospermum australe: Insights from network pharmacology, chemical analysis, and in vitro assays - Andrea Salinas; Christa Burgos; Aaron Rodríguez-Ramos; Alberto Burgos-Edwards; Nelson Alvarenga; Pablo H. Sotelo; Patricia Langjahr (PLoS ONE, 2025)
Inflammation plays a crucial role in homeostasis and defense responses; however, exaggerated and chronic inflammation contribute to the development and worsening of various diseases. Acanthospermum australe (Loefl.) Kuntze ( A. australe ) is a medicinal plant traditionally used to alleviate inflammation. However, the anti-inflammatory activity of this plant has not yet been explored. This study aimed to evaluate the immunomodulatory activity of this species using network pharmacology, UPLC-ESI-MS/MS analysis, and in vitro assays. Network pharmacology analysis revealed the involvement of immune system processes, and among the main targets of A. australe related to inflammation were innate immune responses, toll-like receptors (TLRs), and T cell receptor signaling pathways. A methanolic extract was prepared and analyzed using UPLC-ESI-MS/MS, and 15 compounds were detected. Additionally, the potential targets of A. australe predicted by network pharmacology analysis were validated in vitro using monocytic THP-1 cells and splenocytes. The RT-qPCR analysis indicated that A. australe significantly inhibited the production of pro-inflammatory cytokines IL-1β, IL-6, and TNF-α, as well as chemokine CCL-2, in lipopolysaccharide (LPS)-stimulated cells. Finally, the extract significantly decreased concanavalin A (ConA)-induced T cell proliferation. Overall, our study provides evidence for the anti-inflammatory effects of this species and highlights its mechanisms of action.